Regression of a symptomatic thoracic disc herniation with a calcified intervertebral disc component - Hidayet Sari; Tugce Ozekli Misirlioglu; Deniz Palamar (Acta Orthopaedica et Traumatologica Turcica, 2016)
There were only a few cases describing spontaneous regression of calcified thoracic disc herniation in the literature. We present a 38-year-old male office worker who had left paramedian-foraminal extruded disc at T7–T8 with calcifications of the T7–T8 and T8–T9 intervertebral discs. This case was unique in that the non-calcified extruded disc material regressed almost completely in 5 months while the calcified intervertebral discs remained the same during the process of regression. This report stresses that regression of the herniated material of the thoracic discs with subsidence of the symptoms is still possible even if the disc material is calcified. Keywords: Calcification, Pathologic, Herniated disc, Intervertebral disc, Thoracic vertebrae